Hypocalcaemia and traumatic coagulopathy: an observational analysis. Issue 2 (17th December 2019) - Vasudeva, Mayank; Mathew, Joseph K.; Fitzgerald, Mark C.; Cheung, Zoe; Mitra, Biswadev
Abstract : Background and Objectives: Haemorrhage‐associated calcium loss may lead to disruption of platelet function, intrinsic and extrinsic pathway‐mediated haemostasis and cardiac contractility. Among shocked major trauma patients, we aimed to investigate the association between admission hypocalcaemia and adverse outcomes. Materials and Methods: Data were extracted from the Alfred Trauma Registry and the Alfred Applications and Knowledge Management Department for all adult major trauma patients presenting directly from the scene with a shock index ≥1 from 1 July 2014 to 30 June 2018. Patients with pre‐hospital blood transfusion were excluded. Ionized hypocalcaemia was defined as <1·11 mmol/l, and acute traumatic coagulopathy was defined as initial INR >1·5. Multivariable logistic regression analysis was used to assess the association between admission hypocalcaemia and acute traumatic coagulopathy that was adjusted for Injury Severity Score, initial GCS, bicarbonate and lactate. Results: There were 226 patients included in final analysis with 113 (50%) patients recording ionized hypocalcaemia on presentation prior to any blood product transfusion. Ionized hypocalcaemia was associated with coagulopathy in patients with shock index ≥1 (adjusted OR 2·9; 95% CI: 1·01–8·3, P = 0·048). Admission ionized hypocalcaemia was also associated with blood transfusion requirement in the first 24 h post‐admission in 62·5% of hypocalcaemic patients as compared to 37·5% of normocalcaemic patients ( P < 0·001). Admission ionized hypocalcaemia was associated with death at hospital discharge (25·6% among hypocalcaemic patients compared to 15·0% of normocalcaemic patients ( P = 0·047)). Conclusion: Hypocalcaemia was a common finding in shocked trauma patients and was independently associated with acute traumatic coagulopathy. The early, protocolized administration of calcium to trauma patients in haemorrhagic shock warrants further assessment in randomized controlled trials.